Overexpression of Methylenetetrahydrofolate Dehydrogenase 1 (MTHFD1L) in Colorectal Cancer: A Potential Therapeutic Target. (21st September 2018) - Wang, Kai; Duncan, Virginia; Agarwal, Sumit; Varambally, Sooryanarayana; Peker, Deniz
Abstract: Objectives: Methylenetetrahydrofolate dehydrogenase 1 (MTHFD1L) possesses three distinct enzymatic activities: methylenetetrahydrofolate dehydrogenase, methenyltetrahydrofolate cyclohydrolase, and formate–tetrahydrofolate ligase. Each of these activities catalyzes one of three sequential reactions in the interconversion of 1-carbon derivatives of tetrahydrofolate, which are substrates for methionine, thymidylate, and de novo purine syntheses. Cancer cells rely on the purine through de novo pathway for synthesis of adenine and guanine, whereas normal cells favor the salvage pathway. Thus, MTHFD1L could be a target for anticancer drug design. This study aimed to examine MTHFD1L expression in tubulovillous adenoma (TVA) and colorectal cancer (CRC). Methods: We compared expression of MTHFD1L in 36 samples of CRC, 35 samples of TVA, 9 samples of metastatic CRC, and 7 samples of normal colon. Tissue microarray blocks were constructed and slides were subjected to immunohistochemical staining for MTHFD1L using rabbit anti-MTHFD1L antibody using standard immunohistochemistry methods. Samples were scored for cytoplasmic staining from negative (0) to 3+ positive. Results: All seven normal colon samples had a negative stain of MTHFD1L. Seven of the 35 (20%) TVA cases had a staining intensity of 3+, three of which had high-grade dysplasia. Nineteen of the 35 (54%) TVAs had a staining intensity of 2+. Six of the 35 (17%) TVA cases had a staining intensity of 1+, while three (9%) TVAs had negative staining. Thirty-one of the 36 (86%) CRC cases had a staining intensity of 3+. Three of the 36 (8%) CRCs had a staining intensity of 2+ and one CRC case (3%) had a staining intensity of 1+. Only one (3%) CRC case was negative for the stain. All nine metastatic CRC cases (100%) had a staining intensity of 3+. Conclusion: The results strongly suggest that MTHFD1L could be important in the biology of CRC and a potential target for therapy.